2017
DOI: 10.1126/sciadv.1602372
|View full text |Cite
|
Sign up to set email alerts
|

Tuning across the BCS-BEC crossover in the multiband superconductor Fe 1+ y Se x Te 1− x : An angle-resolved photoemission study

Abstract: A BCS-BEC crossover in a multiband superconductor has been observed experimentally using ARPES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 37 publications
8
76
0
Order By: Relevance
“…It was found experimentally that the dimensionless measure of the pairing strength, i.e. the ratio of the energy gap and the Fermi energy ∆/E F = 0.16, 0.3 and 0.5, increases monotonically with decreasing arXiv:1907.13344v1 [cond-mat.supr-con] 31 Jul 2019 of the iron excess y, exhibiting a crossover from the BCS to the BEC regime 23 . The investigation of the vortex core by means of scanning tunneling microscopy (STM) shows the presence of Friedel-like oscillations, confirming the BCS-BEC crossover nature of FeSe and a peculiar missing of the pseudogap 24 .…”
Section: Introductionmentioning
confidence: 99%
“…It was found experimentally that the dimensionless measure of the pairing strength, i.e. the ratio of the energy gap and the Fermi energy ∆/E F = 0.16, 0.3 and 0.5, increases monotonically with decreasing arXiv:1907.13344v1 [cond-mat.supr-con] 31 Jul 2019 of the iron excess y, exhibiting a crossover from the BCS to the BEC regime 23 . The investigation of the vortex core by means of scanning tunneling microscopy (STM) shows the presence of Friedel-like oscillations, confirming the BCS-BEC crossover nature of FeSe and a peculiar missing of the pseudogap 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In a realistic scenario, presence of additional symmetry breaking terms, such as Rashba cou- pling, is expected to further stabilize the unusual mixed symmetry states reported here [43]. [44,45]. These predictions can also be tested using ultracold Fermions on optical lattices where the interaction strength can be tuned with the help of Feshbach resonances [46][47][48][49].…”
Section: (C)-(d)mentioning
confidence: 83%
“…In fact, this crossover has been realized in ultracold Fermi atomic gases [17,18], and currently, various properties and fluctuation phenomena of this system have been investigated theoretically and experimentally [19][20][21]. Interestingly, recent experiments of FeSe multi-band superconductors also indicated that this electron system is in the BCS-BEC crossover regime [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Considering a two band configuration, where a strongly interacting shallow band is coupled with a weakly interacting deep band through the pair-exchange couplings [46], we show the evolution of the critical temperature, momentum distribution functions, chemical potential, and occupation number densities in each band. This specific band configuration is physically motivated by FeSe superconductors, which are believed to locate in the BCS-BEC crossover regime with a strongly interacting shallow band [35] and for which the BCS-BEC crossover can be tuned by chemical doping [24]. Therefore, we systematically investigate thermodynamic quantities in the two band model by changing the interaction in the shallow band from weak to strong.…”
Section: Introductionmentioning
confidence: 99%